Harmonizing the Settlement of Authority Dispute Between Government Institutions in Indonesian Tax Law - Agus Suharsono (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Governmental institution obligatorily delivers taxing information to Tax Directorate General constituting an administrative law domain, but the imposition of taxing criminal sanction is considered as less appropriate. Settlement of authority dispute between government institutions in Indonesian tax law was not harmonious as it was not based on Governmental Administrative Law. It could be seen that Governmental Administrative Law has not been included into Academic Draft of Tax General Provision and Procedure Law as the material of substantive evaluation so that the settlement of authority dispute has not considered yet the provision of Article 16 or article 21 of Governmental Administrative Law, but taxing criminal law was imposed directly. This study recommended the Governmental Administrative Law to be included into Academic Draft of Tax General Provision and Procedure Law as the material of substantive evaluation to enable the settlement of authority dispute between governmental institutions based on administrative law. Keywords: Authority Dispute, Taxing Criminal Law, State Administrative Law.